2016
DOI: 10.1186/s40814-016-0072-0
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Activation Therapy for Depression after Stroke (BEADS): a study protocol for a feasibility randomised controlled pilot trial of a psychological intervention for post-stroke depression

Abstract: BackgroundThere is currently insufficient evidence for the clinical and cost-effectiveness of psychological therapies for treating post-stroke depression.Methods/DesignBEADS is a parallel group feasibility multicentre randomised controlled trial with nested qualitative research and economic evaluation. The aim is to evaluate the feasibility of undertaking a full trial comparing behavioural activation (BA) to usual stroke care for 4 months for patients with post-stroke depression. We aim to recruit 72 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Participants who did not have moderate or severe language problems were asked to complete the standard version of the EQ-5D-5L as well as an amended (and as yet unvalidated) accessible version (based on pictures). 57 Participants who had moderate to severe language problems were asked to complete the accessible version of the EQ-5D-5L. In addition, for participants who had carers, the carer was asked to complete a standard EQ-5D-5L by proxy.…”
Section: Discussionmentioning
confidence: 99%
“…Participants who did not have moderate or severe language problems were asked to complete the standard version of the EQ-5D-5L as well as an amended (and as yet unvalidated) accessible version (based on pictures). 57 Participants who had moderate to severe language problems were asked to complete the accessible version of the EQ-5D-5L. In addition, for participants who had carers, the carer was asked to complete a standard EQ-5D-5L by proxy.…”
Section: Discussionmentioning
confidence: 99%
“…However, these trials involved people early after stroke and excluded those with severe communication or cognitive problems. The CALM (Communication and Low Mood) trial27 of behavioural therapy demonstrated improved mood in patients with stroke with aphasia, and a feasibility study of behavioural activation is now under way using a broader sample of people with depression 3–60 months poststroke 28. A study of cognitive behavioural therapy (CBT) for poststroke depression demonstrated no benefits over usual care or an attention control; however, the sample size was small 29…”
Section: Introductionmentioning
confidence: 99%
“…BA has shown strong effects both individually (d = 0.78) and in group (d = 0.74) settings in the non-ABI population [25,37,38] as well as preliminary support (d = 0.27 to 0.71) in one-to-one therapy in stroke [34] but this is the rst group BA evaluation, of which we are aware, in ABI. There are clear economic advantages to groups compared with individual therapy [39].…”
Section: Introductionmentioning
confidence: 81%
“…Reduced activity engagement is an important factor contributing to the elevated rates of depression and low mood in ABI [28][29][30][31][32] and thus interventions aimed at improving activity engagement are well-suited toward this population. Promising work examining BA in the speci c context of stroke is already underway [33,34]. In a re-analysis of randomised controlled trial data, Bombardier and colleagues [35] concluded that environmental rewards from daily activities correlated with decreased depression, suggesting the BA-style interventions may be appropriate in TBI as well.…”
Section: Introductionmentioning
confidence: 99%